A discret and devoted pastor : Mgr Paul Etoga : model of life and ecclesial and political committment for priests and bishops in Cameroon - (:unkn) unknown (My University, 2022)
Paul Etoga, first Bishop of Cameroon and Sub-Saharan Africa of French colonisation ruling is studied in interdisciplinary way including theology, ecclesiology, even canon law. Trained and ordained Priest, and later Bishop, in a political and ecclesial context of crisis – due to colonization ruling, independence struggle, discrimination between local and European clergy – he is a symbol of a courageous and caring pastor who succeeded in reconciliating tradition and evangelical requirements. Free and selfless, he campaigns for the recognition of local clergy and human dignity in the way of “politically apolitical” awareness. His nationalism was of eschatological aim. So, in a country and continent in which Church appears going down on its knees in front of the political power, he embodies sacerdotal and episcopal dignity in the way of evangelical priesthood and commitment. His ecclesial and political testimony is of substantive exemplary nature for the Catholic Church in Cameroon and Africa.
Keywords: African Research